A doorway to Borromean halo nuclei: the Samba configuration - Yamashita, Marcelo Takeshi [UNESP]; Frederico, T.; Hussein, M. H. (World Scientific Publ Co Pte Ltd, 2006)
We exploit the possibility of new configurations in three-body halo nuclei, Samba type (the neutron-core form a bound system) as a doorway to Borromean systems. The nuclei Be-12, B-15, N-23 and F-27 are of such nature, in particular N-23 with a half-life of 37.7 s and a halo radius of 6.07 fm is an excellent example of Samba-halo configuration. The fusion below the barrier of the Samba halo nuclei with heavy targets could reveal the so far elusive enhancement and a dominance of one-neutron over two-neutron transfers, in contrast to what was found recently for the Borromean halo nucleus He-6 + U-238.
Keywords: halo nuclei; three-body system; doorways